Hungarian Monitoring, 10 May 1990 . [Magyar rádiófigyelő], 1990. május 10 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Warning strike in the GDR - NATO conference in Canada - Iranian-American hostage conflict - Soviet blockade against Lithuania - Bulgarian election campaign grows more bitter - Mongolian Parliament debate about the presidential election Domestic Affairs: - The Foreign affairs committee recommendations for Hungary to exit the Warsaw Pact - Árpád Göncz's US visit - The Open Skies conference ends without agreement - Csurka and Kenedi about the populist - Urbanist debate Economy: - Hungary can receive World Bank loan Külpolitika: - Figyelmeztető sztrájk az NDK-ban - NATO-konferencia Kanadában - Iráni - Amerikai túszügy - Szovjet blokád Litvánia ellen - Bulgáriában elfajult a választási kampány - A mongol parlament a köztársasági elnökválasztásról vitázik Belpolitika: - A külügyi bizottság javaslata a Varsói Szerződésből való kilépésre - Göncz az Egyesült Államokba látogat - Egyezmény nélkül zárul a Nyitott Égbolt konferencia - Csurka és Kenedi a népi-urbánus ellentétről Gazdaság: - Világbanki hitelekben részesülne a magyar állam